2018
DOI: 10.1080/1061186x.2018.1531419
|View full text |Cite
|
Sign up to set email alerts
|

Phage-displayed peptides targeting specific tissues and organs

Abstract: Phage display is a powerful and widely used technique to find novel peptide ligands. A massive amount of peptide sequences have been identified for all kinds of materials, and peptides that may have targeting capabilities towards specific cells and tissues have received special attention in biomedical sciences. As a result, it is increasingly harder to follow all the work that has been done, which sometimes leads to many promising ligands receiving little attention, together with the publication of false posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 136 publications
0
23
0
Order By: Relevance
“…In contrast, small targeting moieties such as short peptides provide lower chance of immunogenicity due to lack of Fc region, increased ligand multivalency, and easy production by peptide synthesis methods [222][223][224]. Techniques such as phage display provides a means for identifying specific peptide sequences able to target selective tissues or cells [225,226]. A variety of peptides can be used either to target cell surface markers or subcellular elements in vivo.…”
Section: Targeting Peptides In Gdssmentioning
confidence: 99%
“…In contrast, small targeting moieties such as short peptides provide lower chance of immunogenicity due to lack of Fc region, increased ligand multivalency, and easy production by peptide synthesis methods [222][223][224]. Techniques such as phage display provides a means for identifying specific peptide sequences able to target selective tissues or cells [225,226]. A variety of peptides can be used either to target cell surface markers or subcellular elements in vivo.…”
Section: Targeting Peptides In Gdssmentioning
confidence: 99%
“…SAM fabrication is very useful and robust, thus some recent studies have attempted to mimic collagen structures from ECM-derived binding peptides, which increased cell adhesion and cardiac repair by cardiac progenitor cells [154]. These systems can work with other self-assembling materials like phage display peptides and genetic materials to improve adhesion, proliferation, and controlled differentiation; rendering many applications in tissue engineering [155]. Wang et al reported a procedure to fabricate biomaterials for 3D scaffold formation based on SAMs from bacteriophage display [156].…”
Section: Biomaterials and 3d Scaffold Fabricationmentioning
confidence: 99%
“…Recent studies have demonstrated only a single biopanning process is needed for simultaneously selecting affinity peptides against multiple tissues or organs (Andrieu, Re, Russo, & Nicotra, 2019;Staquicini et al, 2009). Moreover, a clinical trial of biopanning against human organs in patients has been successfully performed by Krag et al (2006).…”
Section: Selecting Targeting Peptide/protein From Phage Librarymentioning
confidence: 99%